Automated RVE computations for evaluation of microdamage initiation in structural stitched non-crimp fabric composites. (December 2020) - Pierreux, Gerrit; Hemelrijck, Danny Van; Massart, Thierry J
This contribution presents an approach to generate unit-cell models of structural stitched non-crimp fabric composites. Resin-rich regions and out-of-plane undulations caused by the stitching yarn are represented by initially straight discretised lines, while the stitching yarn is represented initially by a single discretised line which can be transformed into a multi-line configuration to model stitch cross-section variations. The discretised lines are shaped by geometrical operations with a contact treatment and boundary conditions being used to account, respectively, for line interactions and to control the shape of the bottom and top surfaces of each lamina respectively. A fiber-reinforced distorted zone with local variations in fiber volume fraction and fiber direction is modelled in cross-sections of the lamina in a post-processing step. Models for different stacking sequences and stitching parameters are then automatically generated and subsequently being in the stiffness calculation and damage initiation assessment using finite element based mechanical simulations.